2022
DOI: 10.1371/journal.pone.0269299
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study to examine factors influencing COVID-19 vaccine acceptance, hesitancy and refusal in urban and rural settings in Tamil Nadu, India

Abstract: The second wave of the COVID-19 pandemic left the Indian healthcare system overwhelmed. The severity of a third wave will depend on the success of the vaccination drive; however, even with a safe and effective COVID-19 vaccine, hesitancy can be an obstacle to achieving high levels of coverage. Our study aims to estimate the population’s acceptance of the COVID-19 vaccine in an Indian district. A pilot community-based cross-sectional study was conducted from March-May 2021. The data was collected from eight pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Those with lower levels of schooling, wage stagnation, and aged 25 to 54 had a higher likelihood of denying the COVID-19 vaccine. Concerns and postponements about the safety of immunisation were the primary reasons for fostering scepticism about the acceptance of immunisation for COVID-19 [ 19 ]. In another study by Chandania S et al, 25% of people were either oblivious to immunisations or unsure about receiving them, and 10% said they would not accept the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with lower levels of schooling, wage stagnation, and aged 25 to 54 had a higher likelihood of denying the COVID-19 vaccine. Concerns and postponements about the safety of immunisation were the primary reasons for fostering scepticism about the acceptance of immunisation for COVID-19 [ 19 ]. In another study by Chandania S et al, 25% of people were either oblivious to immunisations or unsure about receiving them, and 10% said they would not accept the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“… Acceptance of the COVID-19 vaccine in India according to residence, as shown in the form of a forest plot [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. …”
Section: Figurementioning
confidence: 99%
“…Previous studies have reported that an increase in the proportion of people living in multidimensional poverty reduces COVID-19 vaccination coverage [25]. Also, vaccine hesitancy tends to be influenced by numerous factors like gender, education, occupation, and socio-economic status, which usually leads to a rural disadvantage [26][27][28].…”
Section: Types Of Vaccinesmentioning
confidence: 99%
“…According to research on risk perception and behavior, those who do not have a favorable attitude toward COVID-19 vaccination find the virus less threatening ( 11 ). The intention to be vaccinated is also included under the influence of cognitive assessments (probability of outcome) ( 18 ), race and ethnicity ( 19 21 ), perceptions of risk and susceptibility to COVID-19 ( 22 ), ease of availability and access ( 23 , 24 ) and socio-economic and socio-demographic status ( 15 , 18 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are lots of reason to reject, delay, hesitancy and refusal of COVID-19 vaccine: Fear of short or long term applications to health, not considering being in a risk group, pregnancy, risk pregnancy, recent abortion, breastfeeding period ( 25 ), misinformation beliefs ( 26 , 27 ), not having enough vaccine-related information ( 26 28 ), concerns over vaccine safety ( 18 , 19 , 26 , 28 , 29 ), structural barriers ( 28 , 30 ), personal experience with the disease ( 31 , 32 ), possible unknown future adverse effects of the vaccine ( 32 , 33 ), social determinants of health ( 23 ), low health literacy ( 23 , 34 ), not trusting the drug companies ( 23 , 27 , 29 ), political ideologies ( 11 , 23 , 35 ), distrust of science and the government ( 19 , 26 , 29 , 33 ). Also, various social media made people hesitate to inject the vaccine by spreading false rumors about the COVID-19 vaccine harms, which could create a major challenge for the health system ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%